FAKTORYANG MEMENGARUHI KINERJA BIDAN DESA TERHADAPPEMBERIANIMUNISASI HB-0 DI WILAYAH KERJA DINAS KESEHATAN KOTA SUBULUSSALAM TAHUN 2018 - Cut Poppy Meutia; Tri Niswati Utami; Asiyah Simanjorang (Prodi Kesehatan Masyarakat Fakultas Kesehatan Masyarakat UIN Sumatera Utara, 2018)
Hepatitis B disease is an infectious disease caused by Hepatitis-B Virus (VHB) can be prevented through HB-0 immunization in newborn infants aged 0-7 days whose coverage is still low. District Health Office with six puskesmas achievement of HB-0 immunization under 50% only Simpang Kiri (55,9%) and Sultan Daulat (50,7%) PHC but also not yet reached 90% target.The purpose of this research is to analyze the influence of age, length of work, knowledge, attitude, motivation and job design on midwife performance in HB-0 immunization. The type of research is mixed method with quantitative and qualitative approach aimed at qualitative data give more deep idea for quantitative result. Population is midwives poskesdes amounted to 82 people and all samples used as research. Qualitative researcher as much as 10 people. Qualitative data were analyzed by univariate, bivariate and multivariate. Qualitative data is analyzed through data reduction, display data and conclusion drawing / verification.The results showed that there were influence of working factor (p = 0,022), attitude (p = 0,046), motivation (p = 0,015), and job design (p = 0,035) to midwife performance in HB-0 immunization but age and knowledge has no effect. Qualitative analysis that low HB-0 immunization is due to low family support factor especially husband does not give permission, fear of baby experiencing deman and pity, perception of society which assume HB-0 vaccine haram, and evaluation not followed up.It is recommended that Midwife poskesdes menswiping and cooperate with other health facilities to attract new mothers give birth.Keywords: Performance of Poskesdes Midwife, Immunization HB-0